BP. - Renaudin, Yves; Bernard, Christian (Nice : Villa Arson, Centre National des Arts Plastiques, 1987)
Bellon, Richard ; Layrac, Renaud ; Pohl, Frédéric
Galerie de l'École, Villa Arson, Nice, 17 october - 2 novembre 1986 ; Espace Culturel Albert Camus, La Valette-du-Var, 23 janvier - 20 février 1987
kunstcatalogus